Basic field production sound recording - Lee, Colin; Jasek, Richard; Wheatley, Jason; First Light Video Publishing; Australian Film Television & Radio School ([Australia] : AFTRS, 1992)
Explained basic field of production and focused on sound recording includes mixing, auditing and so on
Title from cover
Camera operator, Sarah Wood ; sound recordist, Damiah Rice
Interviewer: Rosemary Traynor
Keywords: Sound in motion pictures; Television and video photography; Film and video production; Sound -- recording and reproducing; Cinematography